Motivation Level of Construction Workers in Batam City on Maslow’s Theory - Ade Jaya Saputra; Fealy Chia (Universitas Internasional Batam, 2021)
One of the movers of the success of the company’s products is human resources. Generally owner gives motivation to his workers. However, not all workers have same motivation. This research is to describe the results of the level of work motivation based on Maslow’s theory consisting of physiological, safety and security, love or belonging, esteem, and self-actualization. Data were collected by distributing questionnaires to 8 construction companies in Batam City. The highest level motivation needs is physiological with percentage of 5.87%, in the second place there is esteem with percentage of 5.62%. The third rank is love or belonging with percentage 5.41%. Last rank is safety and security with percentage 3.93%.